Disabilities inclusive education systems and policies guide for low- and middle-income countries - Bulat, Jennae; Hayes, Anne M. (RTI Press, 2017)
Having a disability can be one of the most marginalizing factors in a child’s life. In education, finding ways to meet the learning needs of students with disabilities can be challenging, especially in schools, districts, regions, and countries with severely limited resources. Inclusive education—which fully engages all students, including students with disabilities or other learning challenges, in quality education—has proven particularly effective in helping all students learn, even while challenges to implementing inclusive education systems remain. This guide provides suggestions for developing inclusive education systems and policies, especially for low- and middle-income countries that are moving from a segregated system toward an inclusive system of education. We specifically address the needs of countries with limited resources for implementing inclusive education. However, our strategies and recommendations can be equally useful in other contexts where inclusive education practices have not yet been adopted.
Keywords: ⛔ No INSPIRE recid found

Universal Design for Learning to Help All Children Read: Promoting Literacy for Learners with Disabilities - Hayes, Anne; Turnbull, Ann; Moran, Norma (USAID, 2018)

Using Information Communication Technologies (ICT) to Implement Universal Design for Learning (UDL) - Banes, David; Hayes, Anne; Kurz, Christopher; Kulshalnagar, Raja (University Research Co., LLC, 2019)

Using information communications technologies (ICT) to implement universal design for learning - Banes, David; Hayes, Anne; Kurz, Christopher; Kushalnagar, Raja (USAID, 2019)